Preliminary epidemiological analysis on children and adolescents with novel coronavirus disease (2019-nCoV) in a central area of Calabria region - Talarico, Valentina; Nicoletti, Angela; Sabetta, Lucilla; Minchella, Pasquale; Raiola, Giuseppe (Acta Biomedica Atenei Parmensis, 2020)
not available